TINJAUAN DALAM RENCANA PEMBERLAKUAN GREEN TAX ATAU ECO TAX DI INDONESIA UNTUK MENGHADAPI ASEAN ECONOMIC COMMUNITY 2015 - Eva Mustika Pratiwi, Eva; Setyawan, Gadhang (Program Studi Akuntansi FPEB UPI, 2014)
ASEAN Economic Community (AEC) is a community of nations in Southeast Asia who are members of ASEAN. In addition to cooperation in the economic field, the ASEAN Economics Community is also working in the field of defense and security as well as social and cultural. In the socio-cultural cooperation, ASEAN Community is also concerned about environmental decline. One of the policies that can be used to overcome this problem is Green Tax or Eco Tax while the instrument can be used for environmental management ISO 14000. This study uses descriptive qualitative research methods research by studying the symptoms, then the problem interpret or infer meaning a combination of various problems as presented by the situation based on the relevant studies. This research aims to analyze the benefits of the imposition of the Green Tax or Eco Tax in Indonesia and analyze the implementation of the Green Tax or Tax Eco good so it can accommodateÂ entrepreneurs interested and the environment in the face of ASEAN Economic Community 2015.